Use of jump set in relationship to the competition level in male volleyball - Palao, J. M.; Martínez, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The jump set is a technique used by volleyball setters to try to have better conditions for their spikers against blockers. The purpose of this study was to find out the effect of the jump set on set efficacy, reception efficacy, number of players in the block, and efficacy of the play. The sample was composed of eight setters (five setters from the Spanish senior national second division, and four setters from the international senior level -Olympic Games-). A descriptive, transversal and intergroup study design was used. The variables studied were: level of competition (senior national, and senior international), set efficacy, type of set, reception efficacy, number of blockers, and result of the play. The results show that in the use of jump set is higher in the highest level of competition, that it use in this level of competition involves more efficacy in the set, higher number of attack against individual block, done close to the net, and its use increases the options to win the game.